(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2020)
The contribution focuses on the role of reformer of Cornelio Bentivoglio of Aragon, prince of the Church, scholar and protector of writers. The high prelate from Ferrara, after having animated the revival of the Italian theater, got into personal competition against the criticisms made by the French to the Italian epic with the translation of the Thebaid of Statius. The vulgarization re-proposed the Tasso and Renaissance model but updated to a contemporary taste, that refers, on the one hand, the debt with the poetics of the sublime pseudo-Longinian; on the other, to political current events, because of an “ideological” reading of the ancient poem, which alludes to the lacerations made in the body of Christianity by the reformed doctrines. Which Bentivoglio had faced directly in the years of his militancy as pontifical nuncio in Paris.